ANALISIS ISI LAMBUNG IKAN LAIS PANJANG LAMPUNG (Kryptopterus apogon) DI DESA MENTULIK SUNGAI KAMPAR KIRI DAN DESA KOTA GARO SUNGAI TAPUNG PROVINSI RIAU - Meliawati '; Roza Elvyra; Yusfiati ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The study on stomach content of lais panjang lampung fish (Kryptopterus apogon) in Mentulik village of Kampar Kiri River and Kota Garo village of Tapung River was conducted from October 2013 to March 2014. This study aimed to observe the stomach content of lais fish which were categorized into main food, supplement food, and additional food, as well as to determine the ratio of the length of gut toward total body length. The method used in this study was a survey method. The analysis indicated that the food which had the highest value in index of preponderance in both stations based on the type of food and sex was those of animal debris. Furthermore, analysis on the ratio of the length of gut towards the total body length showed that the length of gut never exceed the total body length. Based on the analysis of index of preponderance and the ratio of the length of gut towards the total body length, lais panjang lampung fish (K. apogon) was considered carnivorous.